Keeping Abreast of the Multiple Biological, Cultural, and Psycho-Social Barriers to Breastfeeding in Modern Society - Ping, Elizabeth (Kultura-Społeczeństwo-Edukacja, 2014)
Breastfeeding provides good-quality nutrition for babies and can be very beneficial for both mom and baby. However, modern women face many challenges in breastfeeding their babies that can be attributed to today’s ever-evolving cultural and psycho-social underpinnings. These multiple barriers to breastfeeding in today’s society hinder women from developing a good breastfeeding relationship with their babies. The various factors that prohibit initiation and prolonged breastfeeding however can be counteracted by examining the barriers to breastfeeding and finding reasonable methods for resolving the challenges. Twenty-first century women who desire to breastfeed can be successful at achieving their breastfeeding goals with greater support by society and by having more confidence in themselves.